(untitled) (Journal of Engineering Studies and Research, 2022)
Geophysical survey for groundwater was conducted in two newly built halls of residence (hostels) named Dangote and Shehu Idris at the second phase of Ahmadu Bello University (ABU), Zaria in Nigeria. The vertical electrical sounding (VES) technique of resistivity method was employed with Schlumberger array in seven VES points distributed within the two hostels. Results showed that 4 to 6 geoelectric layers exist within the study area for a spacing of at most 200 m between current electrodes. The resistivity values of the geoelectric layers in all the VES points ranged from 26.6 Ωm – 30342 Ωm while the thickness and depth ranged from 0.263 m – 40.34 m and 0.572 m – 50.66 m respectively. However, four VES points (two in each hostel) were identified to be suitable for borehole drilling though, three out of these four VES points have single aquifer in each with resistivity and thickness ranging from 34.4 Ωm – 40.57 Ωm and 2.02 m – 7.49 m respectively. Conversely, the fourth VES point has two aquifers positioned at the third and fifth layers with resistivity values ranging from 26.6 Ωm – 51.4 Ωm and thickness ranging from 1.93 m – 18.7 m. It was recommended that among the four VES points (two in each hostel) identified to contain aquifers, priority should be given to the ones with larger thickness in each hostel.